1999
DOI: 10.1007/s000110050463
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines in foods: Histamine and food processing

Abstract: Biogenic amines, e.g. histamine, occur in many different foods. At high concentrations, they are risk factors for food intoxication, whereas moderate levels may lead to food intolerance. Sensitive persons, with insufficient diamine oxidase activity, suffer from numerous undesirable reactions after intake of histamine containing foods. Besides spoiled foodstuffs, especially fermented foods tend to contain elevated levels of biogenic amines, although their concentrations vary extensively not only between differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(186 citation statements)
references
References 15 publications
3
173
0
10
Order By: Relevance
“…Removal of the alpha-carboxyl group from amino acid leads to the corresponding biogenic amine 3 . Biogenic amines are undesirable in all foods and beverages and when absorbed at relatively high concentrations, they can induce headaches, respiratory distress, heart palpitations, hyper or hypotension, and several allergenic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Removal of the alpha-carboxyl group from amino acid leads to the corresponding biogenic amine 3 . Biogenic amines are undesirable in all foods and beverages and when absorbed at relatively high concentrations, they can induce headaches, respiratory distress, heart palpitations, hyper or hypotension, and several allergenic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The main BA associated with wine are putrescine, histamine, tyramine and cadaverine (Čuš et al, 2011; 2013), followed by phenylethylamine, spermidine, spermine, agmatine and tryptamine (Smit, 2008). Histamine, tyramine and especially putrescine were found in some wines by Buňka et al (2012) and by Čuš et al (2011; 2013), while the white wines showed lower content of BA in comparison to the red wines (Table 1) (Bodmer et al, 1999). Table 1.…”
Section: Biogenic Amines (Ba)mentioning
confidence: 97%
“…Table 1. : Comparison of biogenic amines concentration (mg l -1 ) in red and white wine (Bodmer et al, 1999).…”
Section: Biogenic Amines (Ba)mentioning
confidence: 99%
“…Activity of foodborne decarboxylases and unwanted microbial activity must be suppressed, while fermentation is performed under strict control by selected, decarboxylase negative starter cultures. Finally, the whole production process should be embedded in a specific quality control procedure and quality management system, including analytical control at critical points (Hungerford et al, 1997;Bodmer et al, 1999).…”
Section: Low Histamine Technologymentioning
confidence: 99%